Can renal ultrasonography and DMSA scintigraphy be used for the prediction of irreversible histological lesions of the upper pole in duplex system with ureteroceles or ectopic ureters? - Smakal, Oldrich; Sarapatka, Jan; Hartmann, Igor; Vencalek, Ondrej; Flogelova, Hana; Koranda, Pavel; Student, Vladimir (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2016)
AIM: To assess of the role of renal ultrasonography (US) and DMSA renal scintigraphy in the prediction of irreversible histological lesions of the upper pole in duplex system. METHODS: A prospective cohort study based on data collected between 2005 and 2012 at our institution. The cohort consisted of 23 patients with ureteroceles and 28 patients with ectopic ureters who underwent upper pole nephrectomy. Preoperative recordings from ultrasound and nuclear renal scans were compared with the histological findings. Histological irreversible lesions were defined as the presence of dysplasia and/or severe chronic interstitial nephritis (CIN) in ≥ 90% of the specimen. ROC (Receiver Operating Characteristic) curves were used to investigate thresholds in order to identify irreversible lesions using various differential functions. The histology was correlated with the results of imaging. RESULTS: Pathological findings were found in all histological samples. Histological lesions were irreversible in 20/23 patients (87.0%) with ureteroceles and in 14/28 patients (50.0%) with ectopic ureters. The model is able to predict irreversible lesions if an upper pole differential function is ≤ 3% in patients with ureteroceles, and ≤ 2% in the presence of ectopic ureters. Weak association between parenchymal thinning on ultrasonography and irreversible lesions was found in patients with ectopic ureters. CONCLUSION: DMSA renal scintigraphy provides a useful tool for the prediction of irreversible lesions in the upper pole. Low differential function (≤ 3% and ≤ 2%, respectively) indicates irreversible lesions, favoring heminephrectomy. Higher differential function indicates greater remaining biological potential of the parenchyma, favoring reconstruction of the upper pole.
Keywords: ultrasonography; ectopic ureter; kojenec; ROC Curve; mužské pohlaví; renal scintigraphy; duplex kidney; Infant; Prospective Studies; ROC křivka; Succimer; dítě; kyselina dimerkaptojantarová; Child; Child, Preschool; ultrasonografie; ženské pohlaví; Radionuclide Imaging; Humans; předškolní dítě; prospektivní studie; ureterocele; ureter; ledviny; radioisotopová scintigrafie; Ureterocele; Ultrasonography; Kidney; Female; Ureter; lidé; Male; ureterokéla